Applying Quality Function Deployment concepts in Anabtawi factory ( Al- Safi company ) - Mousa, Rami; Ibraheem, Murad; Masri, Omar; Ali, Mohammad (My University, 2017)
The need to understand customer requirements and translate them into the design of these needs in a way that suits the wishes of customers is very important for companies, in our project we aim to translate the requirements of customers to design the requirements of a vegetable oil product at Al Safi. Where through the detailed definition and evaluation of the primary customer requirements of Al-Safi oil product with its competitors and determine the technical requirements of the product in order to prioritize its development. In this project we will develop the Al-Safi oil product according to the wishes of the customers by using the dissemination of the quality function and (competitive comparison) by comparing the Al-Safi oil product with the competitors and developing the points in which the product of the competitors applies to the Al-Safi product by setting the objectives and strategies to reach a product with advantage High competitiveness at the local level is the highest level of competition. The research ended with some conclusions. The most important is the weakness of the company in the definition of accurate customer requirements and expectations and the presence of some points in the product need to develop.